(untitled) (Tribhuvan Journal, 2025)
Shadowing in education has been developed in Nepal since the inception of the formal education. It has cultural and traditional basis as our education system developed with Gurukul Shikshya where the education was possible living with the Gurus and serving them to learn and adopt their culture and get educated. This paper is a survey study that focuses on the reasons of getting shadow education by the university level students who gave information on the basis of their experiences of getting shadow education during their school education days. The information was gathered from 400 students studying in different universities in Butwal, Pokhara and Kathmandu through a questionnaire. The students stated the major reasons of getting shadow education and the most common and on the face, the reason was the academic development but the students also have different reasons for being closer to the teachers with other intentions as well, like getting support in exams, getting clues about the important questions, getting better marks in practical examinations etc., which are supposed to be unethical practices in academia. Thus, it is recommended that there should be some controlling mechanism for the teachers and students for not being unethical and keeping shadow education as pure and systematic as the formal education.[This paper is a part of a research conducted with the funding by University Grants Commission (UGC) Nepal with Faculty Research Grant (FRG).]